Recurrent hybridization and gene flow shaped Norway and Siberian spruce evolutionary history over multiple glacial cycles - Qiujie Zhou; Piyal Karunarathne; Lili Andersson‐Li; Chen Chen; Lars Opgenoorth; Katrin Heer; Andrea Piotti; Giovanni Giuseppe Vendramin; Elena Nakvasina; Martin Lascoux; Pascal Milesi (Molecular Ecology, 2024)
Most tree species underwent cycles of contraction and expansion during the Quaternary. These cycles led to an ancient and complex genetic structure that has since been affected by extensive gene flow and by strong local adaptation. The extent to which hybridization played a role in this multi‐layered genetic structure is important to be investigated. To study the effect of hybridization on the joint population genetic structure of two dominant species of the Eurasian boreal forest, Picea abies and P. obovata , we used targeted resequencing and obtained around 480 K nuclear SNPs and 87 chloroplast SNPs in 542 individuals sampled across most of their distribution ranges. Despite extensive gene flow and a clear pattern of Isolation‐by‐Distance, distinct genetic clusters emerged, indicating the presence of barriers and corridors to migration. Two cryptic refugia located in the large hybrid zone between the two species played a critical role in shaping their current distributions. The two species repeatedly hybridized during the Pleistocene and the direction of introgression depended on latitude. Our study suggests that hybridization helped both species to overcome main shifts in their distribution ranges during glacial cycles and highlights the importance of considering whole species complex instead of separate entities to retrieve complex demographic histories.